Hypertrophy-type Resistance Training Improves Phase Angle in Young Adult Men and Women - Ribeiro, Alex Silva; Avelar, Ademar; Santos, Leandro dos; Silva, Analiza Monica; Gobbo, Luis Alberto [UNESP]; Schoenfeld, Brad J.; Sardinha, Luis B.; Cyrino, Edilson Serpeloni (Georg Thieme Verlag Kg, 2017)
The main purpose of the present study was to investigate the effect of a hypertrophy-type resistance training protocol on phase angle, an indicator of cellular integrity, in young adult men and women. 28 men (22.2 +/- 4.3 years, 67.8 +/- 9.0 kg and 174.2 +/- 6.8 cm) and 31 women (23.2 +/- 4.1 years, 58.7 +/- 12.1 kg and 162.7 +/- 6.4 cm) underwent a progressive RT for 16 weeks (2 phases, 8 weeks each), 3 times per week, consisting of 10 to 12 whole body exercises with 3 sets of 8-12 repetitions maximum. Phase angle, resistance, reactance and total body water (intra and extracellular water compartments) were assessed by bioimpedance spectroscopy (Xitron 4200 Bioimpedance Spectrum Analyzer). Total body water, intracellular water and phase angle increased significantly (P < 0.05) in men (7.8, 8.3, and 4.3 %, respectively) and women (7.6, 11.7, and 5.8 % respectively), with no significant difference between sexes (P > 0.05). Bioimpedance resistance decreased (P < 0.05) similarly in both sex (men = -4.8 %, women = -3.8 %). The results suggest that regardless of sex, progressive RT induces an increase in phase angle and a rise in cellular hydration.
Keywords: strength training; phase angle skeletal muscle; cellular hydration; spectral bioimpedance